Different neural substrates at first impressions of same-sex and opposite-sex faces in women. (14th September 2019) - Kim, Hesun Erin; Hong, Yeon-Ju; Kyeong, Sunghyon; Kim, Jae-Jin
Highlights: The formation of first impressions in female participants was examined. Females engage diverse brain regions when viewing male faces than female faces. Lingual activity shows negative parametric effect with cheerfulness for male targets. Inferior parietal activity shows positive parametric effect with good-looks for female targets. There is sex bias in women during friendship encounters. Abstract: First impressions follow a complex process that is greatly influenced by the facial attributes and the sex of the displayer. This study aimed to evaluate whether the initial impression formed in friendship decisions is processed differently between the same-sex and opposite-sex targets in women. Twenty-four healthy female volunteers participated in a functional magnetic resonance imaging experiment, in which they appraised a given face and decided whether they wanted to befriend the target. Then, a post-scan subjective rating was performed for facial components such as cheerfulness, good-looks, and uniqueness. The data were used to perform univariate whole-brain analysis to identify the neural substrates of sex bias in impression formation, and exploratory parametric modulation analysis to examine the parametric effects of facial components. Results showed that a composite of diverse areas including the dorsolateral prefrontal cortex, dorsomedial prefrontal cortex, anterior cingulate cortex, and posterior superior temporal sulcus were more engaged when viewing male faces than female faces. Parametric analysis revealed that bilateral lingual gyrus activities showed a negative parametric effect with cheerfulness for male faces, whereas left inferior parietal lobule activity showed a positive parametric effect with good-looks for female faces. During the formation of first impressions, diffuse areas related to emotion processing and conflict-monitoring were utilized when a person of the opposite sex was encountered compared to encounters with a person of the same sex. The perceived cheerfulness of a male face also showed a negative relationship with the identification of facial emotion in the male face; the more a female face was considered good-looking, a greater feeling of uneasiness appeared to be elicited. The findings from this study provide further evidence of sex bias in women during friendship encounters.